Adaptation of Wetland Rice to Extreme Weather - Dulbari, Dulbari; Santosa, Edi; Sulistyono, Eko; Koesmaryono, Yonny (Department of Agronomy and Horticulture, IPB University, 2017)
Climate change is believed to increase the intensity and the frequency of extreme weather events in reference to strong winds and heavy precipitations. The extreme event is defined as strong wind at speed of 50 km.h-1 and rain fall intensity 10 to 20 mm.h-1 or more . This condition is detrimental to rice production as this may lead to lodging and flooding which normally occurs during the grain filling stage to harvesting resulting in lower yield and grain quality. The. Simultaneous extreme events and critical rice growth occured more frequently due to increasing cropping season within a year in Indonesia. Therefore, it is important to mitigate and develop adaptation strategies in order to sustain rice production. Efforts to adapt to these extreme environmental conditions are mostly based on genetics and agro ecological approaches. Genetically, rice with strong hills, high aerodynamic with low water retention is desired. Agro-ecological manipulation is conducted through wind break application, planting arrangement to facilitate better sunshine penetration, to manage water level and planting calendar. Availability of weather station in the field is important to improve mitigation and continuous adaptation strategy against extreme weather events. Keywords: plant canopy architecture, climate change, heavy rainfall, lodging, strong wind